Entrepreneurial and Inclusive Leadership in Enhancing Employee Innovation in the UAE Oil and Gas Sector - Alsalhi, Rashed Essa Almas Abdulla; Mustapha, Yanti; Hilmi, Mohd Faiz (Aptisi Transactions On Technopreneurship (ATT), 2026)
This study examines the critical role of leadership and innovation in fostering innovative behavior among employees within the UAE oil and gas industry. Using a quantitative approach, the research analyzes the relationships between knowledge sharing, psychological empowerment, entrepreneurial leadership, inclusive leadership, and job insecurity with employee innovative behavior. Additionally, it investigates the moderating effects of nationality, verbal rewards, and material rewards on these relationships. Data were collected through a survey of 380 employees across various oil and gas companies in the UAE and analyzed using Structural Equation Modeling (SEM). The findings reveal that knowledge sharing, psychological empowerment, entrepreneurial leadership, and inclusive leadership all have a significant positive impact on employee innovative behavior, while job insecurity negatively affects innovative behavior. Nationality was found to moderate the relationship between knowledge sharing and innovation, while verbal rewards negatively moderated the relationship between entrepreneurial leadership and innovation. Material rewards had no significant effect. These findings emphasize the importance of entrepreneurial and inclusive leadership in creating an innovative organizational culture, as well as the role of psychological empowerment and knowledge sharing in driving innovation, while job insecurity can hinder employee creativity. The study provides insights for organizations to foster a supportive environment that enhances innovation and sustains competitiveness.